2006
DOI: 10.1007/s00109-006-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expression profiling of human inflammatory cardiomyopathy (DCMi) suggests novel therapeutic targets

Abstract: The clinical phenotype of human dilated cardiomyopathy (DCM) encompasses a broad spectrum of etiologically distinct disorders. As targeting of etiologyrelated pathogenic pathways may be more efficient than current standard heart failure treatment, we obtained the genomic expression profile of a DCM subtype characterized by cardiac inflammation to identify possible new therapeutic targets in humans. In this inflammatory cardiomyopathy (DCMi), a distinctive cardiac expression pattern not described in any previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 62 publications
6
69
0
Order By: Relevance
“…However, previous studies have also implicated Cyr61 in the pathogenesis of inflammatory diseases, such as atherosclerosis (9), inflammatory cardiomyopathy (10), and Graves' ophthalmopathy (11). In a rat model of bacteria-induced apical periodontitis, we found that osteoblastic expression of Cyr61 correlates with the severity of inflammation-associated bone loss (12).…”
mentioning
confidence: 58%
“…However, previous studies have also implicated Cyr61 in the pathogenesis of inflammatory diseases, such as atherosclerosis (9), inflammatory cardiomyopathy (10), and Graves' ophthalmopathy (11). In a rat model of bacteria-induced apical periodontitis, we found that osteoblastic expression of Cyr61 correlates with the severity of inflammation-associated bone loss (12).…”
mentioning
confidence: 58%
“…Studies have connected deregulations of CCN1 to a variety of diseases associated with chronic inflammation, such as rheumatoid arthritis [27], atherosclerosis [28], infectious myocarditis [29], inflammatory bowel disease [30], chronic obstructive pulmonary disorder [31] and several cancers [7]. However, experimental studies have also suggested a role for CCN1 in acute inflammation by demonstrating its ability to promote cytokine secretion [21,32] and support the adhesion of platelets [33], and monocytes/macrophages [21,34].…”
Section: Discussionmentioning
confidence: 99%
“…271 The overexpression of CCN-1 in experimental autoimmune myocarditis confirms the potential role of CCN-1 on leukocyte behavior by decreasing cardiac inflammation. 272,273 Finally, although the in vivo effects of CCN-4 upregulation after MI remain unclear, in vitro studies suggest a role for CCN-4 in fibroblast proliferation and transduction of prohypertrophic and prosurvival signals in cardiomyocytes.…”
Section: Ccn Familymentioning
confidence: 99%